APPLICATION OF THE FINGER GRIP RELAXATION TECHNIQUE TO REDUCE PAIN INTENSITY POST DEXTRA MAMAE TUMOR OPERATION: A CASE STUDY - Kristi Dayanti; Amrih Widiati (Jurnal SMART Keperawatan, 2024)
Mammary tumor is a group of abnormal cells in the breast that grow multiple times. These cells then form a mass/lump in the breast. Nursing problems that can occur in post-operative mammary tumor sufferers are; acute pain related to surgical incisions, disturbed sleep patterns, impaired skin/tissue integrity, anxiety related to crisis situations, risk of infection related to risk factors for leukopenia (Smeltzer, 2018). This scientific paper aims to enable researchers to provide an explanation regarding nursing care using the finger grip relaxation technique to reduce pain intensity in patients post surgery for right breast tumors in Mrs. S at the Bhakti Wira Tamtama Hospital. The research method uses the case study method. The study subject is an individual, namely Mrs. S patient post surgery for dextra mammary tumor. The focus of this case study is the application of finger grip relaxation techniques to reduce pain intensity in post-operative patients with dextra mammary tumors. The location for collecting case study data was at Bhakti Wira Tamtama Hospital on January 22-23 2024. The research results showed that nursing diagnoses were made based on complaints and results of examinations carried out on mammary tumor patients in the patient's medical records, the diagnosis made was acute pain. In conclusion, the application of the finger grip relaxation technique was effective in reducing pain intensity in post-operative patients with right breast tumors in Mrs. S (pain scale decreased from 7 to 3).